My Easter book - Randall, Ronne; Brooks, Nan (New York : Golden Books, 1997)
This festive book introduces very young children to the traditions of Easter--from dyeing Easter eggs to getting dressed up for church to hunting for candy treats--and captures the excitement little ones feel on this special day."--Cover.
Keywords: Easter stories